2021
DOI: 10.3389/fimmu.2021.619362
|View full text |Cite
|
Sign up to set email alerts
|

Novel Secreted Protein of Mycoplasma bovis MbovP280 Induces Macrophage Apoptosis Through CRYAB

Abstract: Mycoplasma bovis causes important diseases and great losses on feedlots and dairy farms. However, there are only a few measures to control M. bovis-related diseases. As in other mycoplasma species, this is predominantly because the virulence related factors of this pathogen are largely unknown. Therefore, in this study, we aimed to identify novel virulence-related factors among the secreted proteins of M. bovis. Using bioinformatic tools to analyze its secreted proteins, we preliminarily predicted 39 secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…The findings are in partial agreement with previous work that M. bovis-induced apoptosis in epithelial cells (MAC-T and EBL cells) via a mitochondria-dependent pathway and ER-stress-dependent signaling pathway, respectively (Liu et al, 2020;Wu et al, 2021). Consistent with our previous study, live M. bovis P1 induced around 14-15% apoptosis in BoMac cells (Zhao et al, 2021). However, we found that the attenuated strain P150 induced significantly more apoptosis than the wildtype strain P1-infected BoMac cells.…”
Section: Discussionsupporting
confidence: 93%
“…The findings are in partial agreement with previous work that M. bovis-induced apoptosis in epithelial cells (MAC-T and EBL cells) via a mitochondria-dependent pathway and ER-stress-dependent signaling pathway, respectively (Liu et al, 2020;Wu et al, 2021). Consistent with our previous study, live M. bovis P1 induced around 14-15% apoptosis in BoMac cells (Zhao et al, 2021). However, we found that the attenuated strain P150 induced significantly more apoptosis than the wildtype strain P1-infected BoMac cells.…”
Section: Discussionsupporting
confidence: 93%
“…This result strongly suggested that rGUDIV-103 played an important role in generating a humoral response in the host by producing specific antibodies. Recombinant proteins from other Mollicutes, such as Mhp597 from M. hyopneumoniae [ 62 ], MbovP280 from M. bovis [ 63 ], surface proteins (MAG_1560, MAG_6130, and P40) from M. agalactiae [ 37 ], and GrpE from U. urealyticum [ 64 ], also induce antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…U. diversum inoculations frequently induce TNF-α , IL-1β , and IL-6 expression [ 31 , 76 ]. Pro-inflammatory cytokine stimulation associated with TLR2 and TLR6 activation or expression has been defined in several Mollicutes species that infect diverse hosts [ 35 , 63 , 68 , 74 ]. Although TLR2 seems to play an important role in the production of pro-inflammatory cytokines, strong evidence indicates that signalling via TLR4 is directly associated with IL-1β and TNF-α expression when macrophages are inoculated with total LAMP extracts, viable U. diversum , or heat-inactivated U. diversum [ 4 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to determine the functions of these proteins is difficult because most of them are putative proteins, and efficient genetic tools and animal infection models for confirmation are lacking. To date, the functions of only a small portion of mycoplasma secreted proteins have been demonstrated, such as P80 of M. hominis [ 24 ], the Community Acquired Respiratory Distress Syndrome (CARDS) toxin [ 25 ], and Mpn491 nuclease [ 26 ] of M. pneumoniae , the apoptosis inducer MbovP280 of M. bovis [ 27 ], and secreted serine protease S41 of M. capricolum [ 28 ].…”
Section: Introductionmentioning
confidence: 99%